The Influence of Google Lens-Assisted Discovery Learning Model on Improving Students' Mathematical Connections - Hidayatsyah Hidayatsyah; Muhammad Fikry; Said Fadlan Anshari; Sudirman Sudirman (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
This study aims to analyze the effect of the Discovery Learning learning model assisted by Google Lens on improving students' mathematical connections. This study used a quasi-experimental method with a Non-equivalent Control Group Design involving high school/vocational high school students in Lhokseumawe City. The sample consisted of an experimental group using Google Lens and a control group using conventional learning. The results showed a significant increase in mathematical connection skills in the experimental group compared to the control group. Students' perceptions of the use of Google Lens were also positive, with indicators of increased learning motivation and engagement. These findings provide implications for the implementation of technology in mathematics learning.